Effects of Extender and Storage Time on Motility and Ultrastructure of Cooled-Preserved Boar Spermatozoa - Duangjai Boonkusol; Kulnasan Saikhun; Poonsuk Ratanaphumma (Agriculture and Natural Resources, 2010)
Artificial insemination (AI) using fresh diluted semen is used worldwide in the porcine industry. Viability of spermatozoa in diluted semen depends on several factors, such as the interaction with the type of extender and storage duration. The aim of this study was to evaluate the effects of extenders and storage time on the motility and ultrastructure of cooled-preserved boar spermatozoa. Semen samples were collected, diluted in BTS, Merck III or Androhep and stored at 15°C for 0, 1, 3, 5 and 7 d. The samples were warmed (37°C) and spermatozoa were evaluated for motility using light microscopy and ultrastructure using scanning (SEM) and transmission (TEM) electron microscopy. The results showed that motility did not differ significantly (P>0.05) among extenders at days 0 to 3, while Androhep showed a significantly (P<0.05) higher percentage of motility than BTS and Merck III from days 5 to 7. At day 7 of semen storage, plasma and acrosomal membrane damage were observed, as revealed by SEM and TEM. These findings suggest that the type of semen extender and cooled-preserved time affected motility and caused structural damage to boar permatozoa, especially in the plasma and acrosomal membrane.